In Situ Thermal Remediation: State of the Practice in South America - Kessel, Lowell Gerardo (Águas Subterrâneas, 2011)
A review of the three primary methods for in situ thermal remediation will be reviewed and include Thermal Conductive Heating, Electro Thermal Dynamic Stripping Process (ET-DSP) or Electrical Resistance Heating, and Steam Injection and Stripping. Each of these ISTR approaches are successful under the correct site conditions and for destruction of specific target organic contaminants. However, no single ISTR technology is appropriate for all applications.